2017
DOI: 10.1128/mbio.01415-17
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + T Cells Orchestrate Lethal Immune Pathology despite Fungal Clearance during Cryptococcus neoformans Meningoencephalitis

Abstract: Cryptococcus neoformans is a major fungal pathogen that disseminates to the central nervous system (CNS) to cause fatal meningoencephalitis, but little is known about immune responses within this immune-privileged site. CD4 ϩ T cells have demonstrated roles in anticryptococcal defenses, but increasing evidence suggests that they may contribute to clinical deterioration and pathology in both HIVpositive (HIVϩ) and non-HIV patients who develop immune reconstitution inflammatory syndrome (IRIS) and post-infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
112
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 71 publications
(84 reference statements)
9
112
0
1
Order By: Relevance
“…Another important variable affecting patient outcomes may be immune dysregulations that could either reduce microbial clearance or result in inflammatory syndromes, similar to cryptococcal immune reconstitution inflammatory syndrome (cIRIS) after antiretroviral therapy (ART) in HIV-related disease or a postinfectious inflammatory syndrome in non-HIV patients (15,29,30) which is also present during murine infections (31). In the present study, CAmB treatment in the presence of CM resulted in small but significant elevations in IL-1␤, the proinflammatory cytokine that had previously been reported to be elevated after exposure to conventional AmB (14,32).…”
Section: Discussionmentioning
confidence: 99%
“…Another important variable affecting patient outcomes may be immune dysregulations that could either reduce microbial clearance or result in inflammatory syndromes, similar to cryptococcal immune reconstitution inflammatory syndrome (cIRIS) after antiretroviral therapy (ART) in HIV-related disease or a postinfectious inflammatory syndrome in non-HIV patients (15,29,30) which is also present during murine infections (31). In the present study, CAmB treatment in the presence of CM resulted in small but significant elevations in IL-1␤, the proinflammatory cytokine that had previously been reported to be elevated after exposure to conventional AmB (14,32).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a clinical study showed that HIV-positive patients with cryptococcal infection developed immune reconstitution inflammatory syndrome after antiretroviral therapy (67). A recent study using a mouse model explicitly demonstrated that CD4 ϩ T cells act as a "double-edged sword" in both killing fungal cells and causing significant immunopathology and mortality to the host during cryptococcal central nervous system infection (68,69).…”
Section: Fig 10mentioning
confidence: 99%
“…Microglia are key effector cells in the host defenses to microbial infections and act as antigen presenting cells that can produce active substances that promote in ammatory cell death [39,40]. Following C. neoformans exposure, microglia produce TNF-α, IL-1β and IL-6 to upregulate MHC Class II and CD11c [41,42]. Moreover, microglia can phagocytose C. neoformans and upregulate iNOS with anti-fungal effects which is dependent on GPR43 expression [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%